Transition of the epidemiological profile of maternal and congenital syphilis in the State of Goiás (2009-2018): a retrospective analysis - Mamede, Lorenna Rocha Lobo e Silva; Silva, Antonio Márcio Teodoro Cordeiro; Almeida, Rogério José de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Syphilis is a bacterial infection transmitted sexually and transplacental. In Brazil, in the last decade, there has been an increase in notifications of maternal (MS) and congenital (SC) syphilis. Aim: To analyze the epidemiological profile of reported cases of GS and CS in the historical series, from 2009 to 2018, in the state of Goiás. Outlining: Epidemiological, cross-sectional, and analytical retrospective study that describes and analyses the data on MS and CS available in the Information System for Notifiable Diseases (SINAN). Contingency tables, descriptive and inferential statistics were presented, with the application of the G Test and significance level ≤0.05. Results: The results highlighted epidemiological changes in the sociodemographic profile and in the data of the care of pregnant women with syphilis. Implications: The evidenced epidemiological transition shows that there was an improvement in prenatal care in the state of Goiás, requiring health policy measures for specific risk groups. It is fundamental to plan and implement strategic actions with the redefinition of priorities in relation to the epidemiologically affected groups.